2009
DOI: 10.1096/fj.09-136457
|View full text |Cite
|
Sign up to set email alerts
|

A fragment of the scaffolding protein RanBP9 is increased in Alzheimer's disease brains and strongly potentiates amyloid‐β peptide generation

Abstract: Increasing biochemical and genetic evidence indicates that the amyloid-beta (Abeta) peptide derived from amyloid precursor protein (APP) plays a central role in Alzheimer's disease (AD) pathogenesis. We previously reported that RanBP9 promotes Abeta generation by scaffolding APP/BACE1/LRP complexes together. Interestingly, the RanBP9-Delta1/N60 (residues 1-392) deletion mutant interacted much more strongly with APP/BACE1/LRP than full-length RanBP9. In this study, we found that RanBP9-N60, a processed form of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
69
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 33 publications
8
69
0
Order By: Relevance
“…Together with our previous demonstration that RanBP9 robustly enhances Ab generation, [6][7][8] these data further implicate the RanBP9-cofilin pathway not only as therapeutic targets to stem Ab generation but also block the neurotoxic effects of Ab.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Together with our previous demonstration that RanBP9 robustly enhances Ab generation, [6][7][8] these data further implicate the RanBP9-cofilin pathway not only as therapeutic targets to stem Ab generation but also block the neurotoxic effects of Ab.…”
Section: Discussionsupporting
confidence: 73%
“…We previously demonstrated that the overall levels RanBP9, particularly the bioactive N-terminal 60 kD fragment (N60), is increased in brains of AD patients compared with the age-matched healthy controls. 8 Thus, we assessed whether RanBP9 levels might be altered in a mouse model of AD pathology. In brains of 10-12-month-old J20 APP transgenic mice carrying both the Swedish and Indiana APP mutations, RanBP9 levels were increased by more than fourfold in J20 mice compared with their non-transgenic counterparts (Figures 1a and b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, RanBP9 was found to be within the clusters of RNA transcript pairs associated with markers of AD progression, suggesting that RanBP9 might contribute to the pathogenesis of AD (9). In fact, even before this finding, we showed for the first time that RanBP9 protein levels are increased 6-fold in AD brains (10) and that RanBP9 overexpression increases A␤ generation 4-fold in cell cultures by increasing ␤-secretase-mediated processing of APP (11) and also increases amyloid plaques in mouse brains (12), which, in turn, leads to a significant loss of synaptic proteins (12). Because RanBP9 is known to exist in large multiprotein complexes of greater than 670 kDa (13,14), we speculated that A␤ generation may be modulated by several other RanBP9-binding proteins.…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 52%